Network dynamics of positive energy districts: a coevolutionary business ecosystem analysis - Zapata Riveros, Juliana; Scacco, Paulet Michelle; Ulli-Beer, Silvia (Frontiers in Sustainability, 2024)
Amid the rising interest in sustainable urban development, Positive Energy Districts (PEDs) have become a focus of research. This study examines the dynamic processes that influence the development and scalability of PEDs from a co-evolutionary business ecosystem perspective. Applying the business ecosystem framework to the Hunziker Areal case study, we developed and validated a high-level conceptual model through workshops and guided interviews with experts from pilot and research projects. The study reveals key feedback loops, including increasing utility and value creation capacity, CO2 goal achievement and the impact of low prosumer electricity unit cost (PEUC) on technology adoption. Furthermore, we identify factors affecting value capture and attractiveness of the ecosystem for investors. Additionally, the study highlights the crucial role of supportive policies and regulations in facilitating PED diffusion and scalability.The paper highlights the importance of using a systemic approach to assess the potential for using PEDs to improve housing sustainability while creating value for multiple stakeholders. The study uses causal loop diagrams to identify key feedback loops that explain the diffusion of PEDS, shows how the utility of PEDs is perceived differently by different stakeholders who evaluate the impact of PEDs using different KPIs (e.g. CO2 target achievement, well-being, etc.), and identifies key factors that influence technology adoption (e.g. low prosumer electricity unit cost). The study also reveals important aspects that influence value capture and the attractiveness of the ecosystem to investors. In addition, the study highlights the critical role of supportive policies and regulations in facilitating PED diffusion and scalability.